Efektivitas Bimbingan Konseling Islam dengan Metode Alquran dalam Mengatasi Stres dan Kecemasan pada Mahasiswa Program Studi Agama Islam Universitas Muhamadiyah Surakarta - Mahasri Shobibaya; Nuarta Rosa Sasmita (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
In today's fast-paced and busy modern world, anxiety and stress are problems that many people from all walks of life often face. The formation of this disease is often triggered by social and family interactions, work pressure, and economic insecurity. Although many strategies have been created to help people deal with stress and anxiety, a comprehensive approach that can simultaneously combine psychological and spiritual aspects is still needed. In this context, Islamic counseling has been seen as a possible strategy. Islamic counseling combines counseling methods with Islamic spiritual beliefs to address clients' spiritual well-being in addition to mental health problems. Every human being experiences what appears to be an extremely long period of time during his or her adult life in adulthood. A two-group pre-test and post-test design was used in this study. Examination of survey findings before and after the intervention allows researchers to determine how responses vary between experimental and control groups. Six respondents were divided into three experimental groups and three control groups to measure their level of academic anxiety. After that, for a predetermined period of time, the experimental group will receive spiritual therapy intervention, while the control group will not. Research findings support the usefulness and efficacy of Islamic counseling in helping students overcome stress and anxiety, and they suggest that this approach should be expanded in the context of higher education. A study on the effectiveness of Islamic counseling in helping Islamic studies program students at Muhammadiyah University of Surakarta cope with stress and anxiety shows that the this is quite successful. Students who previously experienced quite high levels of stress and anxiety reported a significant reduction in these symptoms after attending a series of counseling sessions that integrated Islamic ideas and concepts. Their ability to face challenges from both personal and academic life, as well as their sense of inner calm and emotional control, all noticeably improved. If this therapy is given correctly and according to the protocol, this therapy can be beneficial for those who undergo it. Several things need to be considered so that this psychological therapy is successful: confident, consistent, sincere, resigned, and grateful. Failure can be added to by one of the five This is the efficacy of Islamic counseling in helping students overcome stress and anxiety, and they suggest that this approach should be expanded in the context of higher education. A study on the effectiveness of Islamic counseling in helping Islamic studies program students at Muhammadiyah University of Surakarta overcome stress and anxiety shows that this strategy is quite successful . Students who previously experienced quite high levels of stress and anxiety reported a significant reduction in these symptoms after attending a series of counseling sessions that integrated Islamic ideas and concepts. Their ability to face challenges from both personal and academic life, as well as their sense of inner calm and emotional control, all noticeably improved. If this therapy is given correctly and according to the protocol, this therapy can be beneficial for those who undergo it. Several things need to be considered so that this psychological therapy is successful: confident, consistent, sincere, resigned, and grateful. Failure can be added to by one of the five This.